2006
DOI: 10.1186/1471-2407-6-287
|View full text |Cite
|
Sign up to set email alerts
|

Etiological study of esophageal squamous cell carcinoma in an endemic region: a population-based case control study in Huaian, China

Abstract: Background: Continuous exposure to various environmental carcinogens and genetic polymorphisms of xenobiotic-metabolizing enzymes (XME) are associated with many types of human cancers, including esophageal squamous cell carcinoma (ESCC). Huaian, China, is one of the endemic regions of ESCC, but fewer studies have been done in characterizing the risk factors of ESCC in this area. The aims of this study is to evaluate the etiological roles of demographic parameters, environmental and food-borne carcinogens expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 46 publications
9
84
0
2
Order By: Relevance
“…We included only studies with case -control or cohort design, the former limited to those that used control subjects without upper gastrointestinal cancers. Using these approaches, we found 55 full-text articles, among which 2 (Wang et al, 1992;Chen et al, 2003) reported the results from 3 and 2 individual studies, respectively, making the total number retrieved 58, of these 24 were excluded because: (i) no risk estimates or crude numbers of cases and controls for the exposureof-interest were reported (Shen et al, 1999;Wang et al, 2006); (ii) the method of pickling vegetables differed from those in East and Southeast Asia (Onuk et al, 2002;Sapkota et al, 2008); (iii) results were only reported in combination with other foods (Hou et al, 1999;Lu et al, 2000;Wang et al, 2004;Xie et al, 2005;Pan et al, 2006) or in combination with other cancers (Li et al, 1989;Yu et al, 1993;Tong et al, 2001;Zhang et al, 2001; one of the three studies reported in Chen et al, 2003); and (iv) results were also reported in other publications (Chu and Ye, 1992;Chu et al, 1992a,b;Guo et al, 1994;Cheng et al, 1995;Li et al, 2001;Xu et al, 2002;Li et al, 2007;Feng et al, 2008a; another one of the three studies reported in Chen et al, 2003). Finally, 34 studies remained in the meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We included only studies with case -control or cohort design, the former limited to those that used control subjects without upper gastrointestinal cancers. Using these approaches, we found 55 full-text articles, among which 2 (Wang et al, 1992;Chen et al, 2003) reported the results from 3 and 2 individual studies, respectively, making the total number retrieved 58, of these 24 were excluded because: (i) no risk estimates or crude numbers of cases and controls for the exposureof-interest were reported (Shen et al, 1999;Wang et al, 2006); (ii) the method of pickling vegetables differed from those in East and Southeast Asia (Onuk et al, 2002;Sapkota et al, 2008); (iii) results were only reported in combination with other foods (Hou et al, 1999;Lu et al, 2000;Wang et al, 2004;Xie et al, 2005;Pan et al, 2006) or in combination with other cancers (Li et al, 1989;Yu et al, 1993;Tong et al, 2001;Zhang et al, 2001; one of the three studies reported in Chen et al, 2003); and (iv) results were also reported in other publications (Chu and Ye, 1992;Chu et al, 1992a,b;Guo et al, 1994;Cheng et al, 1995;Li et al, 2001;Xu et al, 2002;Li et al, 2007;Feng et al, 2008a; another one of the three studies reported in Chen et al, 2003). Finally, 34 studies remained in the meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…33 Wang et al reported that eating fast significantly increased the risk of esophageal cancer with an OR of 3.39 (95% CI: 1.15-9.95). 34 Eating too quickly can cause irritation of the esophageal mucosa and lead to chronic esophagitis, which has been considered an early sign of malignant transformation of the squamous epithelium. 35 Moreover, irritation may increase cell turnover and increase the contact between carcinogens and dividing target cells, thus making the esophagus more susceptible to cancer.…”
Section: Epidemiologymentioning
confidence: 99%
“…Variations in enzyme activity of EPHX1 as a result of such polymorphisms may lead to interindividual variations in susceptibility to chemical carcinogen-induced cancers, including EC. Although some studies have attempted to link EPHX1 gene Tyr113His and His139Arg polymorphisms to EC, the resulting data are not often reproducible (Zhang et al, 2003;Casson et al, 2003Casson et al, , 2006Lin et al, 2006;Wang et al, , 2006Jain et al, 2008;Ihsan et al, 2010;Dura et al, 2012). As a caveat, failure of replication may result from the genetic heterogeneity between different races or ethnicities, as well as individual studies with relatively low statistical power.…”
Section: Introductionmentioning
confidence: 99%
“…Further application of our inclusion/exclusion criteria left 9 articles (Zhang et al, 2003;Casson et al, 2003Casson et al, , 2006Lin et al, 2006;Wang et al, 2003Wang et al, , 2006Jain et al, 2008;Ihsan et al, 2010;Dura et al, 2012), including 8 studies for the Tyr113His polymorphism with 1158 EC cases and 1868 controls Zhang et al, 2003;Casson et al, 2003Casson et al, , 2006Lin et al, 2006;Jain et al, 2008;Ihsan et al, 2010;Dura et al, 2012), and 7 studies for His139Arg with 901 EC and 1615 controls Casson et al, 2003Casson et al, , 2006Lin et al, 2006;Jain et al, 2008;Ihsan et al, 2010;Dura et al, 2012). The detailed selection process and the baseline characteristics of the qualified studies are presented in Figure 1 and Table 1, respectively.…”
Section: Description Of Available Studiesmentioning
confidence: 99%